Decision-aided-based multiple blind PN code estimation algorithm of asynchronous CDMA signal - Zhaoyang QIU; Tianyun LI; Xiangming CHEN (Tongxin xuebao)
Aiming at the problem of blind estimation of multi-user pseudo-code of multi-path asynchronous code division multiple access (CDMA) signal,using the finite element (FA) characteristic of transmitted symbol,a decision aid (DA) method based on maximum likelihood was proposed.A two-step iterative estimation structure for PN code,transmitted bit and channel was designed to realize the estimation of multiple user code in asynchronous CDMA system with superior performance.Moreover,the Cramer-Rao bound (CRB) of PN code estimation in asynchronous CDMA signal was derived to evaluate the performance of proposed method.Simulation indicates significant improvement in performance which is close to the theory bound of the proposed method compared to commonly-used iterative least square with projection (ILSP) method.The method can also achieve superior estimation when the user number increases.